The Effect Aspiration on Students’ Learning Achievement at SMP N 3 Menggala - Baniyah Baniyah; Siti Roudhotul Jannah; Ferdian Utama (Bulletin of Science Education, 2023)
The purpose of this study was to determine the high or low influence of ideals on Islamic education learning achievement of class IX students of SMPN 3 Menggala. The research method used in this journal article is a type of qualitative research using a case study approach, namely to explore information about the relevance or influence of ideals on PAI learning achievement. Based on the results of the research that has been done, it can be concluded that these ideals have a significant influence on student achievement, namely in the subject of Islamic Religious Education (PAI) at SMPN 3 Menggala. Where the results of the analysis indicate a positive correlation, namely between ideals and learning achievement, so that the higher the ideals of a student, the higher the learning achievement. There are several factors that also influence the relationship between aspirations and student achievement in PAI, namely motivation, parental support, environment, and academic ability, as well as financial ability. Therefore these factors should need to be considered by all relevant stakeholders, such as teachers and parents who can play a role in helping students achieve clear and directed goals and improve their learning achievement. Keywords: Students’ Learning Achievement, Effect Aspiration, Learning Achivement